Education and peace - Guerrero Ortiz, Luis (1993)
The text was written by a well-known German pedagogue, Johan Sulzer, in 1748. But the quote is only a sample of the enormous inventory of beliefs regarding the education of children, which Katharina Rutschky gathered in her famous book, "Black Pedagogy". The child should not get used to doing his will. At the base of this simple principle there is certainly a perception of childhood and, therefore, of human nature itself, extraordinarily valid, despite the enormous distance that separates us from the Germany of the 18th century.